HIV Therapy with Unknown HBV Status is Responsible for Higher Rate of HBV Genome Variability in Ethiopia. Issue 2 (February 2017) - Belyhun, Yeshambel; Maier, Melanie; Liebert, Uwe Gerd
Background: In Ethiopia, HBV and HIV are co-circulating. Since patients are not routinely tested for HBV, the use of antiretroviral drugs could contribute to unintended HBV drug resistance and surface gene variability during HIV coinfection. Methods: A total of 161 hepatitis B surface antigen (HBsAg)-positive sera from 58 HIV-coinfected and 103 drug-naive HBV-monoinfected individuals were characterized for HBV drug resistance and immune escape HBsAg variants. HBV polymerase/surface gene fragment of 716 bp was analysed by direct sequencing. Results: In 34 out of 161 study subjects (21.1%) HBV drug resistance mutations (DRMs) were detected with a frequency of 3.1% rtL80F/I, 0.6% rtA181V, 1.2% rtT184S, 6.2% rtV173L, 10.6% rtL180M, 10.6% rtM204V/I and 8.1% rtI233V. The prevalence of the major DRMs in HBV–HIV-coinfected individuals was significantly higher than monoinfected individuals (41.4% versus 10.7%). Lamivudine selected DRMs, that is, rtL180M (29.3%) and rtM204V/I (29.3%) and rtV173L (15.5%) were more prevalent in HBV–HIV-coinfected individuals but absent in HBV-monoinfected individuals. Despite the finding that rtL180M and rtM204V/I were higher among ART-experienced individuals, the overall prevalence of DRMs (48.0% versus 36.4%) showed no significance difference among antiretroviral therapy (ART) status. The study also revealed higher frequency and heterogeneity of putative and known immune escape HBsAg mutations both in the major hydrophilic region (MHR; 68.3%) and outside the MHR (82.5%) of the surface gene. In particular, the 'a' determinant surface gene mutations (sT125S, sA128V, sQ129H/R, sT131I, sC137S, sT143M, sD144D/E, sG145R, sT148P) and the majority of clustered/multiple as well as drug selected immune escape HBsAg mutations were more prevalent in HBV–HIV-coinfected individuals. Conclusions: HIV therapy without HBV co-management in Ethiopia fosters emergence and circulation of HBV variants of public health importance. It is highly recommended to include HBV testing and co-management as part of routine HIV care programmes for a better ART selection.